Shaping Political Awareness: Legal Politics for First-Time Voters in Banten’s Simultaneous Elections - Karsa, Pipih Ludia; Marpudin, Ade (Probono and Community Service Journal, 2024)
Elections are a cornerstone of democracy, reflecting popular sovereignty and the political rights of citizens. Beginner voters, however, often face challenges due to limited knowledge and understanding of electoral processes, especially in the context of simultaneous general elections. This study addresses the urgency of legal political education as a solution to these challenges, focusing on novice voters in Banten Province. Using qualitative methods and analysis of relevant literature and documents, this research highlights the experiences from the 2019 simultaneous elections, offering insights into voter behavior and participation. The Community Partnership Program (PKM) conducted at SMKN 1 Kalanganyar and SMAN 1 Ciomas provided targeted political education, significantly enhancing the knowledge, understanding, and enthusiasm of beginner voters. This initiative underscores the vital role of legal political education in empowering first-time voters and emphasizes the shared responsibility of educational institutions and stakeholders in fostering informed electoral participation.